Extra Virgin Olive Oil Supplementation Reduces Anthropometric Risk Factors for Type 2 Diabetes in Adolescent Girls - Rahmawati, Wenny; Retnaningrum, Dwi Norma (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Type 2 diabetes mellitus in adolescents has increased dramatically, with an incidence increasing from 9 to 18 cases per 100,000 per year in the last two decades. Extra Virgin Olive Oil (EVOO) has been shown to have a protective effect against diabetes through its bioactive components. This study aims to analyze the effect of EVOO supplementation on anthropometric parameters as an indicator of diabetes prevention in adolescent girls. This quasi-experimental study employed a pretest-posttest control-group design. The study population comprised all adolescent girls at SMKN 13 Malang, and subjects were selected through purposive sampling; 30 adolescent girls aged 15-18 years were included. Subjects were divided into an intervention group (n=15) who received 10ml/day of EVOO supplementation for 12 weeks and a control group (n=15) who received no treatment. The parameters measured included body weight, height, and waist circumference. The analysis used paired t-tests and Mann-Whitney tests. The results showed a significant decrease in body weight (p=0.000), BMI (p=0.000), and waist circumference (p=0.000) compared to the control group, which experienced an increase in body weight (0.5 kg) and waist circumference (0.233 cm). Still, there was no significant difference in height (p=0.539). In conclusion, EVOO supplementation is effective in reducing body weight and waist circumference in adolescent girls, demonstrating its potential as a preventive agent for diabetes mellitus through improving body composition.